2001
DOI: 10.1016/s1010-7940(00)00613-8
|View full text |Cite
|
Sign up to set email alerts
|

Experimental use of an albumin–glutaraldehyde tissue adhesive for sealing pulmonary parenchyma and bronchial anastomoses✩

Abstract: This study supports BioGlue to be effective as an adjunct in sealing bronchial anastomosis and lung parenchyma defects in sheep, with minimal secondary healing disruptions such as granuloma formation. The results of this study indicate that the use of BioGlue in human pulmonary surgery should be effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 21 publications
2
44
0
6
Order By: Relevance
“…It is a powerful surgical adhesive that has been used extensively in cardiac, pulmonary, and vascular surgery with excellent results [31][32][33][34][35][36][37]. The BioGlue seeps easily through the porous knitted Vicryl mesh to adhere to the underlying crural tissues.…”
Section: Discussionmentioning
confidence: 99%
“…It is a powerful surgical adhesive that has been used extensively in cardiac, pulmonary, and vascular surgery with excellent results [31][32][33][34][35][36][37]. The BioGlue seeps easily through the porous knitted Vicryl mesh to adhere to the underlying crural tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, it was used in aortic surgery as well as in the treatment of bronchopulmonary fistulas. Later on, it was used in other types of surgery [15][16][17][18][19][20][21][22][23]. Although it has been reported that BioGlue is safe and effective with no or minimal adverse side effects, some reports indicate that BioGlue might cause an inflammatory response [24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…It remains intact for up to 2 years and is then resorbed slowly and replaced by normal tissue [14]. Its use has been well established in other fields of surgery [15][16][17][18][19][20][21][22][23]. Because of the advantages of rapid polymerization, resistance, flexibility and the long durability we decided to use BioGlue as an adjunct to flap repair.…”
Section: Introductionmentioning
confidence: 99%
“…Os autores atribuíram esses efeitos ao glutaraldeido, como puderam comprovar que, mesmo após a sua polimerização, a BioGlue libera consideráveis quantidades de glutaraldeido no líquido sobrenadante, e, a adição desse líquido a diferentes culturas de células, apresentava efeitos deletérios à viabilidade das mesmas. Da mesma maneira, Herget et al 39 , utilizando a BioGlue em anastomoses sobre os brônquios de ovelhas, detectaram uma resposta inflamatória consistindo de neutrófilos polimorfonucleares e macrófagos infiltrando o parênquima pulmonar e a área da anastomose em que a cola foi utilizada, além de necrose tecidual localizada. LeMaire et al 40,41 , demonstraram lesão do nervo frênico quando em contato com a cola, levando a paralisia do diafragma, assim como toxicidade sobre o tecido de condução cardíaca.…”
Section: Parâmetrosunclassified